Validation of fracture envelopes of structural adhesives for mixed-mode strength prediction of bonded joints - Raul Campilho; João Ribeiro; Ricardo Rocha; Alberto Leal; Filipe Viana (Fracture and Structural Integrity)
In the design of adhesive structures, it is extremely important to accurately predict their strength and fracture properties (critical strain energy release rate in tension, GIC, and shear, GIIC). In most cases, the loads occur in mixed-mode (tension plus shear). Thus, it is of great importance the perception of fracture in these conditions, namely of the strain energy release rates in tension, GI, and shear, GII, relative to different crack propagation criteria or fracture envelopes. This comparison allows to determine the most suitable energetic propagation criterion to be used in cohesive zone models (CZM). The main objective of this work is to verify, by CZM, which is the power parameter (a) that best suits the energetic crack propagation criterion for CZM modelling, using single-lap joints (SLJ) and double-lap joints (DLJ) with aluminium adherends and bonded with three different adhesives. With this purpose, numerical simulations of the SLJ and DLJ are carried out, and the maximum load (Pm) is compared with experiments. For the Araldite® AV138 and Araldite® 2015, the energetic criterion resulting from the experimental work provided matching numerical results and, thus, the fracture envelopes were validated. The Sikaforce® 7752 results were slightly offset due to CZM law shape issues.